2009
DOI: 10.1111/j.1471-4159.2008.05796.x
|View full text |Cite
|
Sign up to set email alerts
|

Afamin is synthesized by cerebrovascular endothelial cells and mediates α‐tocopherol transport across an in vitro model of the blood–brain barrier

Abstract: Members of the vitamin E family [a-, b-, c-, and d-tocopherols and -trienols] are transported in association with lipoproteins and/or specific carrier proteins (Kayden and Traber 1993). Dietary vitamin E is absorbed in the proximal intestine, assembled with chylomicrons, and secreted into lymphatic vessels. Chylomicrons are hydrolyzed in the circulation, and Received July 10, 2008; revised manuscript received October 7, 2008; October 30, 2008; accepted November 12, 2008. Address correspondence and reprint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 45 publications
0
48
0
Order By: Relevance
“…3B). From our real-time PCR, we detected an increase in the expression of Afamin, 23 Caps2, 21,22 Slc2a10, 26,27 Sec14l4, 24,25 and P2rx7 [18][19][20] as well as Neurogenin3 28 in the Pdx1 PB -Isl-1-Myc islets (Fig. 3B).…”
Section: β-Cell Function In Pdx1mentioning
confidence: 95%
See 2 more Smart Citations
“…3B). From our real-time PCR, we detected an increase in the expression of Afamin, 23 Caps2, 21,22 Slc2a10, 26,27 Sec14l4, 24,25 and P2rx7 [18][19][20] as well as Neurogenin3 28 in the Pdx1 PB -Isl-1-Myc islets (Fig. 3B).…”
Section: β-Cell Function In Pdx1mentioning
confidence: 95%
“…In this analysis, we were able to detect an increase in Slc2a10 (Glut10), a gene that has been implicated in glucose metabolism and type 2 diabetes, 26,27 increased levels of SEC14L4, a factor that has been implicated to be involved in secretion in organs like salivary gland, prostate and pancreas, 24,25 and a 35-fold increase in Afamin levels, a transporter for α-tocopherol in the CNS. 23 Additionally, P2rx7, a purinergic receptor with implicated function for regulating both endocrine and exocrine pancreas function and Caps2, transgenic mouse line was characterized in our study, which we acknowledged it as a caveat, we are confident that the effects we observe in the Pdx1 PB -Isl-1-Myc mice are due to the elevation of Isl-1 expression as Arx and MafA, two genes that are downregulated in Isl-1 deficient pancreata, 10,11 were increased the islets of the Pdx1 PB -Isl-1-Myc transgenic mice. Animal experiments were approved by the Children's Hospital of Philadelphia's Institutional Animal Care and Use Committee.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kratzer et al discovered afamin expression in cerebrovascular endothelial cells and demonstrated that afamin facilitates vitamin E transport/transfer across the blood-brain barrier in a suitable cell culture model [20], suggesting a role of afamin in the regulation of vitamin E uptake and transport at the blood-brain barrier.…”
Section: Afamin Expression and Occurrence In Human Body Fluidsmentioning
confidence: 98%
“…The role of afamin remains to be determined; however, afamin is considered to influence the uptake and transport of a-tocopherol at the blood-brain barrier, and is thought to have neuroprotective activity (41,42). In the current study, hepatic afamin expression decreased in STZ rats, and therefore the levels of a-tocopherol in distributed fluids are considered to be low in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 70%